Thank u - Morisette, Alanis; WARNER Music (Malaysia). (Kuala Lumpur : Warner Music (M), 1998)
Contains the single taken from the album Supposed Former Infatuation Junkie.
CD 1 : Thank U / (4:18).
Koleksi Khas Wiramanja.
Title from disc label.
Keywords: Songs, English; Rock music